EFFECT OF NEMATODE POPULATION DENSITIES ON TRAPPING ACTIVITY OF NEMATOPHAGOUS FUNGUS Arthrobotrys dactyloides ON Meloidogyne javanica - . Sudirman (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Trapping activities of some nematophagous fungi were suggested to be related to the population density of nematodes. This study determined the trapping activity of Arthrobotrys dactyloides due to the effects of (i) different populations of Meloidogyne javanica, (ii) the presence of Caenorhabditis elegans, (iii) repeated inoculation of M. javanica, and (iv) different populations of both C. elegans and M. javanica. Experiments were conducted using a “standard slide test” and “soil microcosm” inoculated with A. dactyloides formulated in kaolin-alginate granules and with low nematode populations ranged from 6 to 14 juveniles per g soil. Results showed that ring formation and trapping activity of A. dactyloides increased with the increase of M. javanica population. The presence of C. elegans increased M. javanica mortality. Repeated inoculation of M. javanica maintained trapping activity of A. dactyloides. The mortality of M. javanica increased with the increase of both C. elegans and M. javanica population.